Beyond Black - Mantel, Hilary (New York : Picador, 2006)
Colette and Alison are unlikely cohorts: one a shy, drab beanpole of an assistant, the other a charismatic, corpulent psychic whose connection to the spiritual world torments her. When they meet at a fair, Alison invites Colette at once to join her on the road as her personal assistant and companion. Troubles spiral out of control when the pair moves to a suburban wasteland in what was once the English countryside. It is not long before the place beyond black threatens to uproot their lives forever. This is Hilary Mantel at her finest--insightful, darkly comic, unorthodox, and thrilling to read.
"A John Macrae book."
Keywords: Female friendship; Divorced women; Women mediums; Spiritualists; England